Vascular endothelial growth factor B (VEGF-B) binds to VEGF receptor-1 and regulates plasminogen activator activity in endothelial cells - Olofsson, Birgitta (National Academy of Sciences, 1998)
The vascular endothelial growth factor (VEGF) family has recently expanded by the identification and cloning of three additional members, namely VEGF-B, VEGF-C, and VEGF-D. In this study we demonstrate that VEGF-B binds selectively to VEGF receptor-1/Flt-1. This binding can be blocked by excess VEGF, indicating that the interaction sites on the receptor are at least partially overlapping. Mutating the putative VEGF receptor-1/Flt-1 binding determinants Asp(63), Asp(64), and Glu(67) to alanine residues in VEGF-B reduced the affinity to VEGF receptor-1 but did not abolish binding. Mutational analysis of conserved cysteines contributing to VEGF-B dimer formation suggest a structural conservation with VEGF and platelet-derived growth factor. Proteolytic processing of the 60-kDa VEGF-B(186) dimer results in a 34-kDa dimer containing the receptor-binding epitopes. The binding of VEGF-B to its receptor on endothelial cells leads to increased expression and activity of urokinase type plasminogen activator and plasminogen activator inhibitor 1, suggesting a role for VEGF-B in the regulation of extracellular matrix degradation, cell adhesion, and migration.